Pengembangan Katalis Water-Gas Shift: Perspektif dari Sistem Medium Temperature Shift (MTS) - Liska, Salma; Sajida, Gita Nur; Legawati, Lisa; Suhendri, Suhendri; Meldha, Zuqni; Yolanda, Yogi; Hendri, Yola Bertilsya; Rusmana, Marcela Anandita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The water-gas shift (WGS) reaction is a crucial process for increasing hydrogen (H₂) production by minimizing carbon monoxide (CO) content. It is widely applied in the petrochemical industry to reduce CO levels in syngas produced from hydrocarbon reforming. Conventionally, this reaction is conducted in two stages: high-temperature shift (HTS) and low-temperature shift (LTS). However, this approach presents both technical and economic limitations. To address these issues, catalysts capable of operating optimally at intermediate temperatures—referred to as medium-temperature shift (MTS)—have been developed. The scope of discussion in this article consists of catalyst development challenges such as sintering, deactivation, and side reactions. This review is intended to serve as a reference for the development of efficient WGS catalysts under MTS conditions, along with modification strategies aimed at enhancing their performance based on current research findings.